Latihan Plyometric Standing Jump Dan Plyometric Box Jump Meningkatkan Tinggi Lompatan Pada Siswa Ekstrakulikuler Bola Voli SMKN 3 Malang - Linda Ayu Septiani; Slamet Raharjo; Olivia Andiana (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2022)
This study aims to determine the difference between standing jump plyometric exercises, box jump plyometric exercises and control of the jump height of volleyball extracurricular students at SMKN 3 Malang. In this study, the pre-experimental method was used to design two groups pretest posttest and design with control, with the treatment group plyometric standing jump exercises, and the plyometric box jump exercise group, with group selection by purposive sampling. Parameters for measuring jump height using a vertical jump test. The analysis used in this study used the anova test analysis with the help of the SPSS 25 application. The results of this study showed a significant difference between the plymetric standing jump treatment group, plyometric box jump and the control group. The test results between the data using the one-way anova test with a statistical significance result of 0.001 <0.05, which means the data shows a difference. After the Anova test was carried out, the Pasthoc Bonferroni test was carried out to find out which exercise was more effective in increasing jump height. Based on the results of the Pashoc test, it was found that the plyometric standing jump exercise group was more optimal in increasing the jump height compared to the plyometric box jump group and the control group.